A integração regional na África Austral: obstáculos e oportunidades (1980-2008) - Jamine, Elísio Benedito (2010)
This study addresses the current trend of new regional international blocks creation from the point of view of the experience of the Southern African Development Community Comunidade para o Desenvolvimento da África Austral (SADC). We intend to understand its historical development, politic-economics dynamics on the challenges and opportunities for continuous developing and consolidation of this regional block, within regional and continental context. We argue that the past of cooperation between region States and the emergence of the Southern African Development Coordination Conference Conferência de Coordenação para o Desenvolvimento da África Austral (SADCC) was largely in response to trends of South Africa political and economic domination based on its domestic and regional policy of apartheid and on the alliances inserted in the Cold War. While the SADC emerges as an economic-commercial approach than politics, in light of regional challenges and that of the new international order, whose answers are based on regional integration. The study aims to contribute to the understanding of the past and present cooperation and integration in Southern Africa. The approach includes the period from 1980 to 2008